Occurrence and antimicrobial susceptibility of Salmonella isolates from grilled chicken meat sold at retail outlets in Erbil City, Kurdistan region, Iraq - Almashhadany, Dhary A. (Ital J Food Saf, 2019)
Food borne salmonellosis is a major public health problem worldwide. This study aimed to detect the occurrence and antibiotics sensitivity of Salmonella species in grilled chicken meat sold at retail outlets in Erbil City, Kurdistan, Iraq. Two hundred and twenty-five (225) samples were aseptically collected from central and suburb retail outlets. For isolation of salmonellae, samples were cultured on selective media and tested for their susceptibility to common antibiotics by disk diffusion assay. The results revealed that the overall prevalence of Salmonella among grilled chicken meat samples was 7.1%. The isolates belonged to eight different serotypes of Salmonella. These include S. Typhimurium, S. Tennessee, S. Newport, S. Enteritidis, S. Anatum, S. Arizona, S. Muenchen, and S. Montevideo. The antibiotic resistance profile revealed a total resistance to Levofloxacin and total sensitivity to Cefotaxime, Amoxicillin, and Cefadroxil. This resistance among Salmonella may pose a public health hazard that requires effective precautions and response.